The Structural and Morphological Properties of Heat Treated Hybrid Blend ZnPc/CdS Thin Films - Lafta, Hoolya A.; Abdulameer, Ameer F. (Iraqi Journal of Science, 2019)
CdS Nps (inorganic material) was prepared by the chemical reaction method. ZnPc (organic material) and CdS thin films were prepared separately to compare their characterization with the hybrid BHJ blend ZnPc/CdS thin film (2ml:2ml) by spin coating technique. The structural and morphological properties of the prepared thin films have been measured by XRD and AFM respectively. The XRD pattern for both as-deposited and annealed CdS nanoparticle films shows a hexagonal structure. The crystallite size behavior of as deposited ZnPc films and annealing at 423K for 1h, 2h and 3h was approximately similar to the behavior of heat treated blended films. The grain size was measured by AFM, which decreaseds with annealing temperature for ZnPc films, while it increases with annealing for CdS films.